Imaging gaseous detectors and their applications - Nappi, Eugenio (Wiley-VCH, 2013)
Describing advanced detectors and their visualization and investigation techniques, this book presents the major applications in nuclear and high-energy physics, astrophysics, medicine and radiation measurements.